Biofortified b-carotene rice improves vitamin A intake and reduces the prevalence of inadequacy among women and young children in a simulated analysis in Bangladesh, Indonesia, and the Philippines - De Moura, Fabiana F.; Moursi, Mourad; Angel, Moira Donahue; Angeles-Agdeppa, Imelda; Atmarita, Atmarita; Gironella, Glen M.; Muslimatun; Carriquiry, Alicia (Elsevier, 2016)
Background: Vitamin A deficiency continues to be a major public health problem affecting developing countries where people eat mostly rice as a staple food. In Asia, rice provides up to 80% of the total daily energy intake. Objective: We used existing data sets from Bangladesh, Indonesia, and the Philippines, where dietary intakes have been quantified at the individual level to 1) determine the rice and vitamin A intake in nonpregnant, nonlactating women of reproductive age and in nonbreastfed children 1–3 y old and 2) simulate the amount of change that could be achieved in the prevalence of inadequate intake of vitamin A if rice biofortified with β-carotene were consumed instead of the rice consumed at present. Design: We considered a range of 4–20 parts per million (ppm) of β-carotene content and 10–70% substitution levels for the biofortified rice. Software was used to estimate usual rice and vitamin A intake for the simulation analyses. Results: In an analysis by country, the substitution of biofortified rice for white rice in the optimistic scenario (20 ppm and 70% substitution) decreased the prevalence of vitamin A inadequacy from baseline 78% in women and 71% in children in Bangladesh. In Indonesia and the Philippines, the prevalence of inadequacy fell by 55–60% in women and dropped by nearly 30% in children from baseline. Conclusions: The results of the simulation analysis were striking in that even low substitution levels and modest increases in the β-carotene of rice produced a meaningful decrease in the prevalence of inadequate intake of vitamin A. Increasing the substitution levels had a greater impact than increasing the β-carotene content by >12 ppm.